Efficacy and safety of elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide in Asian participants with human immunodeficiency virus 1 infection: A sub-analysis of phase 3 clinical trials. Issue 3 (4th May 2019) - Kim, Yeon-Sook; Oka, Shinichi; Chetchotisakd, Ploenchan; Clarke, Amanda; Supparatpinyo, Khuanchai; Avihingsanon, Anchalee; Ratanasuwan, Winai; Kiertiburanakul, Sasisopin; Ruxrungtham, Kiat; Yang, SangYoun; Guo, Susan; Liu, YaPei; et al.
Abstract : Background: The efficacy and safety of a single tablet regimen (STR) of elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide (E/C/F/TAF) was analyzed in Phase 3 clinical trials in antiretroviral therapy (ART)-naive and ART-experienced Asian participants infected with human immunodeficiency virus (HIV)-1 through 96 or 144 weeks. Objective: In Asian population requiring treatment, it is imperative to have data specific to this group, particularly as there is a general concern that Asians with lower body weight have increased risk of tenofovir disoproxil fumarate (TDF)-related renal dysfunction. Methods: Studies -104 and 111 were randomized, double-blind, placebo-controlled, 144-week studies conducted in ART-naive participants, comparing E/C/F/TAF versus E/C/F/TDF. Study 109 was a randomized, open-label, 96-week study conducted in virologically suppressed, ART-experienced participants, who switched to E/C/F/TAF from ritonavir/cobicistat-boosted atazanavir ATV+(RTV or COBI) + F/TDF regimens, from non-nucleoside reverse transcriptase inhibitors (NNRTI) + F/TDF regimens, or from E/C/F/TDF. Study 112 was a single arm, open-label, 144-week study conducted in HIV suppressed, ART-experienced participants with mild-moderate renal impairment, who switched to E/C/F/TAF. Results: Asian participants in these studies had sustained efficacy safety and tolerability. In Study 104/111, Asian participants achieved 93% virologic suppression on TAF vs 88% on TDF at week 144. At baseline, there were numerically more Asians with median CD4 counts < 200 cells/uL and VL > 100, 000 c/mL. In Study 109, 95% of Asians on TAF vs 86% on TDF maintained virologic suppression at week 96. Lastly, in Study 112, 91% maintained virologic suppression at week 144. There were no discontinuations due to renal AE, no cases of PRT or Fanconi syndrome in any of the studies.